Epidemiology, identification, treatment and return to play of musculoskeletal-based ice hockey injuries - LaPrade, R. F.; Surowiec, R. K.; Sochanska, A. N.; Hentkowski, B. S.; Martin, B. M.; Engebretsen, L.; Wijdicks, C. A. (British Journal of Sports Medicine, 2014)
Ice hockey is a high contact sport where players are inherently at an increased risk for traumatic and time-loss injury. With its increasing popularity and high incidence of injury, further research is necessary to understand the risks and injuries associated with the sport and to develop performance-based outcome measures to guide return to play. This review, tailored to the practicing sports medicine team physician, focuses on the stepwise identification, treatment, time loss, return to play and subsequent risk of injury for the most common areas of injury: the head, shoulder, hip and knee. Injuries were categorised into upper and lower extremity with an emphasis on glenohumeral and acromioclavicular joint injuries, femoroacetabular impingement, medial collateral ligament tears, and high ankle sprains. With return to play a primary goal for these high-level athletes, recovery in ice hockey becomes a complex issue with efficient protocols tailored to the requirements of the sport vital to the athlete and clinician alike. By reviewing the treatments and sport-specific care, athletes can be better managed with the ultimate goal of returning to their preinjury level of play.